OSMIUM ISOTOPIC COMPOSITION OF CORALS: EVIDENCES FOR MULTIPLE SOURCES - SEAWATER OR DIAGENESIS RECORD? - Levasseur S.; Birck J.L.; Allegre C.J. (My University, 1999)
Osmium concentrations in corals are very low (<20 ppt) and large isotopic variations (between 2.92 +- 0.05 9.01 0.05) areobserved indicating sample heterogeneity. these interpreted as a two component mixing for each sample. the unradiogenic has about same value all samples is of mantle meteorite composition concentration. radiogenic composite signal, different resulting fromseawater osmium continental detrital sediment osmium. simple calculations show that micrometeoritic flux 40 20.106 kg/yr is too small by about two orders of magnitude to explain the composition of these samples. In the absence of a potential mantle source for the corals, it is considered that corals, as they filter water for feeding, scavenge meteoritical osmium from seawater.